Effect of Corn Row Spacing on Herbicide Effectiveness for Weed Control in 2022 - S. H. Lancaster; E. Adee (Kansas Agricultural Experiment Station Research Reports, 2023)
Cultural weed control practices such as narrow row spacing can be a key component of successful weed management. Experiments were conducted in the Kansas River Valley to evaluate interactions of herbicide programs and corn row spacings on weed control and grain yield. There were no differences in weed control at a site with low weed density. However, at a site with high Palmer amaranth density, Resicore applied to 15- and 30-inch rows and Bicep + Acuron applied to 15-inch rows resulted in the greatest weed control. Corn yield was similar across all treatments at both locations.
Keywords: corn row spacing; weed control; herbicide